PENGARUH PENINGKATAN KAPASITAS PRODUKSI MI JAGUNG KERING TERHADAP NERACA BAHAN (Effect of Scale up Dried Corn Noodle Production Capacity on Material Balance) - Sholichah, Enny; Indrianti, Novita; Haryanto, Aidil (Jurnal Hasil Penelitian Industri, 2015)
Implementation of dried corn noodle processing technology is required to enrich cornprocessing culture in our sociaty. However improvement of the process is still required to becommercially feasible. In general, scale-up production capacity will affect the operating conditionspecially to the material balance during the production process. Material balance used as a base infinalcial analysis dan feasibility study. This research aimed to study the effects of production capacityscale-up on material balance. In this study the weight of all material during corn noodle processingstages are recorded. The increment of corn noodle production capacities are 3, 4, 5 and 6 kg per batch.The results showed that final yields range from 63.3 to 64.5%. Production capacity scale-up is notsignificantly affected material balance during row material weighing,dough steaming,sheeting-slitting,drying and packaging. Production capacity scale-up increase the process efficiency during doughcompressing and noodle steaming stages, however decrease the mixing stage efficiency.